Meta-analytic structural equation modeling (MASEM): new tricks of the trade - Holger Steinmetz; Jörn Block (Management Review Quarterly, 2022)
Meta-analytic structural equation modeling (MASEM) has become a widespread approach to meta-analyze the evidence in a field and to test a (theoretical) multivariate model based on aggregated data. This editorial presents new tricks of the trade and discusses current issues surrounding MASEM that in our view are either insufficiently recognized in the MASEM literature or present new developments. The editorial is organized in three parts, in which we discuss (a) the goals and causal underpinnings of a MASEM, (b) new possibilities to analyze effect size heterogeneities through moderator variables and (c) the use of statistical tests and p values.
Keywords: C51; C52; 650